The Finnish Ice Service, its sea-ice monitoring of the Baltic Sea and operational concept - Eriksson, Patrick B.; Vainio, Jouni; Tollman, Niko; Jokiniemi, Anni; Arola, Aleksi; Mäkynen, Marko; Karvonen, Juha; Kangas, Antti (Frontiers in Marine Science, 2025)
The Finnish Ice Service is part of the Finnish Meteorological Institute (FMI). Based on the mandate in the Finnish legislation, it provides information on the ice conditions in the Baltic Sea. This paper introduces the methods used by the Finnish Ice Service, data sources, products, services, datasets, and supporting Baltic Sea ice remote sensing and geophysics research conducted at FMI. The predecessor of the Finnish Ice Service started its operational ice charting in 1915 to provide ice information for the winter navigation. To this day, the main users still are the winter navigation authorities, including the icebreaker fleet and management, as well as the shipping community, scientists and general public. The focus area is the Baltic Sea. Typically, the service operates from mid-October to the end of May, providing up-to-date sea-ice information in several products and formats. The prevailing ice situation is described in ice charts, ice reports and ice codes, which are based on a range of different observation sources like satellite images, predominantly from synthetic aperture radars, and surface observations from both icebreakers and coastal observers. The Finnish Ice Service has long sea ice observation timeseries and archives of manually analysed ice charts. To help users and customers optimize their operations in ice infested waters, the Finnish Ice Service provides numerical and manual sea ice forecasts with various forecast lengths. The Finnish Ice Service processes and disseminates satellite data and also provides advisory and consultant services to users. As FMI is committed to the open data policy, the main ice service products are provided free of charge. A number of products are also available through the Copernicus Marine Service (CMS).